Relevansi Filsafat Hukum Islam dan Maqāṣid al-Syarī‘ah dalam Menjawab Isu Modern - Prayiani, Herlian Janu; Hasibuan, Edi Saputra (AL-SULTHANIYAH, 2026)
Islamic law is understood as a manifestation of divine will that is normative and transcendent, while also being realized through revealed texts, scholarly interpretation, social practice, and legal institutions. The concept of maqāṣid al-sharī‘ah emphasizes that the objectives of Islamic law are to preserve five fundamental human interests: religion, life, intellect, lineage, and property, as well as secondary and complementary goals aimed at enhancing the moral and ethical quality of society. This teleological approach allows Islamic law to remain flexible, adaptive, and responsive to social, political, and cultural dynamics. Islamic legal philosophy is also relevant in addressing contemporary issues, including human rights, democracy, and the development of digital technology, through the integration of ethics, the principle of public interest (maṣlaḥah), and maqāṣid-based ijtihād. Accordingly, Islamic legal philosophy functions as both a conceptual and practical guide that bridges divine values, rationality, and contextual needs, ensuring that law remains ethical, progressive, and relevant in the construction of a just and civilized society.